Determinantes del uso de las remesas: caso matriz del cantón Cañar - Unach (2019)
A micro-economic analysis is carried out to explain the factors that determine the use of remittances in investment activities in the parent parish of Cañar canton, 2018. Demographic data were collected for a descriptive and econometric analysis. One hundred thirty-seven surveys were conducted to people who are direct recipients of remittances in different institutions such as banks, savings and credit cooperatives and couriers. During the field investigation it was found that approximately 51% is utilized in consumption. Things like food, health and clothing. 41% goes to investments. 6% to the payment of debts and 2% to other items. Through an econometric estimation, it was observed that only one factor, the amount, explains in a positive and significant way that the use of remittances is for investment. For each 1% increase in the number of their remittances received, the use of payments towards finance will increase by approximately $ 1.90.